2022
DOI: 10.31083/j.jin2106155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Basal Ganglia Diseases

Abstract: Objective: Vitamin D (VitD) has been shown to influence several cellular processes in the brain. The extent to which VitD plays a role in the pathomechanism of neuronal loss and dysfunction in basal ganglia diseases (BGDs) is still debated. There is yet to be a comprehensive study that provides an overview of all of the most relevant BGDs. Methods: PubMed, and Google Scholar were systematically searched for observational studies that investigated the association between serum VitD levels and BGDs up to March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Becerra et al describe that two (40%) of their patient’s falls required hospitalization but do not give details about the sustained injuries [ 39 ]. Unfortunately, neither of the authors provided data on bone mineralization or vitamin D levels frequently found diminished in RLS [ 40 41 ], which could have been a possible explanation for the seriousness of the injuries [ 42 43 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Becerra et al describe that two (40%) of their patient’s falls required hospitalization but do not give details about the sustained injuries [ 39 ]. Unfortunately, neither of the authors provided data on bone mineralization or vitamin D levels frequently found diminished in RLS [ 40 41 ], which could have been a possible explanation for the seriousness of the injuries [ 42 43 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have provided encouraging data that VitD3 and Res could be beneficial for restoring normal movement and reducing postural and action tremor of the upper limbs, as well as tremor in the legs and trunk 48 53 . However, to the best of our knowledge, there have been no investigations of the effect of the combination of VitD3 and Res on ET.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, despite these promising indications, scientific data is insufficient to recommend vitamin D as a therapy choice in rehabilitations. Yet, considering the significant frequency of hypovitaminosis D in senior patients with MDs (Homann and Homann, 2022), as well as the demonstrated overall benefit and potential specific impact, Vitamin D management and assessment should become part of standard care for elderly patients with MDs. In this regard, replacement should be sufficient but not excessive, adhering to recommended limits (Rosen et al, 2012;Bouillon, 2017).…”
Section: Implications For Clinical Practicementioning
confidence: 99%